Prevalence of Anxiety and Depression among Nurses Working Nightshift at Hospitals in Kathmandu Valley of Nepal - Chhetri, Dinesh; Paudel, Ashok Kumar; Baniya, Ambika; Thapa, Rashmi; Thapa, Pramila (Journal of Karnali Academy of Health Sciences, 2022)
Background: Nurses professionals experience an overwhelming level of depression and anxiety; which remain taboo, despite the prevalence of these mental health conditions within the field. This cross-sectional hospital-based study was conducted to identify the prevalence of anxiety, depression and associated factors among nightshift working nurses of hospitals in Kathmandu Valley of Nepal. Methods: Cross-sectional hospital-based study was done among randomly sampled nightshift working nurses. Total 206 samples derived by using the formula; n=z²pq/e2. Hospital Anxiety and Depression Scale used to assess the level of anxiety, depression and associated factors. The self-administered Hospital Anxiety and Depression Scale was pretested and finalized before data collection. Nightshift working nurses were respondents and the purpose of the study explained to the respondents before data collection. Verbal informed consent was obtained from nurses and ethical approval from Nepal Health Research Council was taken. Scientific Package for Social Science version-20 used for data analysis and relevant statistical test applied. Results: Mean age of nurses was 24.46 ± 3.7 SD. years Forty-one percent of the nurses were between 22-26 years and 70.9% of them were unmarried. Three in four (75.0%) of nightshift working nurses had anxiety and nearly half (49.5%) of them had depression. Age of the nurses and level of anxiety (p= 0.032); working duration of the nurses and level of depression (p= 0.02) was found significantly associated with the depression. Conclusions: Remarkable proportion of hospital working nurses of Kathmandu Valley has anxiety and depression. Age and working duration of nurses were the factors associated with anxiety and depression respectively. So, there is an insistent need to develop policies, plans and programs to resolve the issues related to the prevalence of anxiety and depression among the hospital working nurses in Kathmandu Valley.